Solving Fractional Diffusion Equation via the Collocation Method Based on Fractional Legendre Functions. (24th July 2014) - Syam, Muhammed; Al-Refai, Mohammed
Abstract : A formulation of the fractional Legendre functions is constructed to solve the generalized time-fractional diffusion equation. The fractional derivative is described in the Caputo sense. The method is based on the collection Legendre and path following methods. Analysis for the presented method is given and numerical results are presented.